Regulating The Shell Thickness of Nitrogen-Doped Hollow Carbon Nanospheres for Enhanced Electrochemical Performance. Issue 3 (1st February 2023) - Xue, Chunjian; Zhao, Jinlian; Liu, Yinpeng; Li, Xiying; Zhang, Jiwei; Zhang, Jingwei
Abstract: The shell thickness of hollow carbon spheres (HCs) plays a vital role in the electrochemical performance due to its direct influence on the transport kinetics of lithium ions. However, it is a tough task to ascertain the contribution solely from the changes of shell thickness but not from the synergistic effect of chemical compositions, pore structures and specific surface area. Herein, a simple one-pot method is developed to synthesize N-doped hollow carbon nanospheres (NHCs) with different shell thickness (6, 10 and 13 nm) while retaining other parameters almost same, such as chemical components, pore structure and specific surface area. The NHCs-1 sample with shell thickness of 6 nm, exhibits initial charge capacity of 1320.1 mA h g −1 at low current density (50 mA g −1 ) and retains capacity of 862.1 mA h g −1 after 500 cycles at high current density (500 mA g −1 ), obviously higher than those of NHCs-2 (717.1 mA h g −1 ) and NHCs-3 (588.9 mA h g −1 ) with the shell thickness of 10 and 13 nm, respectively. The capacity dependent on the shell thickness is detailedly addressed considering the changes of mass transfer coefficient of Li-ion across the wall. Also, the outstanding electrochemical properties of the NHCs can be ascribed to the unique hollow structure, N-doping and high specific surface. Furthermore, the calculation based on oxidation peaks of NHCs samples indicates that the reaction energy barrier gradually reduces with decreasing the shell thickness, which validates the enhancement of Li-ion transfer. The strategy developed for the preparation of hollow carbon spheres with different shell thickness via a simple one-pot method, provides a promising alternative to devise new carbonaceous materials as superior electrode material in the field of energy storage.